Alterations in the intestinal microbiome and metabolic profile of patients with cirrhosis supplemented with lactulose, Clostridium butyricum, and Bifidobacterium longum infantis: a randomized placebo-controlled trial - Haifeng Lu; Xiaofei Zhu; Lingyun Wu; Xiaobin Lou; Xiaxia Pan; Bowen Liu; Hua Zhang; Lingxiao Zhu; Lanjuan Li; Lanjuan Li; Lanjuan Li; Zhongwen Wu (Frontiers in Microbiology, 2023)
BackgroundLiver cirrhosis is commonly accompanied by intestinal dysbiosis and metabolic defects. Many clinical trials have shown microbiota-targeting strategies represent promising interventions for managing cirrhosis and its complications. However, the influences of the intestinal metagenomes and metabolic profiles of patients have not been fully elucidated.MethodsWe administered lactulose, Clostridium butyricum, and Bifidobacterium longum infantis as a synbiotic and used shotgun metagenomics and non-targeted metabolomics to characterize the results.ResultsPatients treated with the synbiotic for 12 weeks had lower dysbiosis index (DI) scores than placebo-treated patients and patients at baseline (NIP group). We identified 48 bacterial taxa enriched in the various groups, 66 differentially expressed genes, 18 differentially expressed virulence factor genes, 10 differentially expressed carbohydrate-active enzyme genes, and 173 metabolites present at differing concentrations in the Synbiotic versus Placebo group, and the Synbiotic versus NIP group. And Bifidobacteria species, especially B. longum, showed positive associations with many differentially expressed genes in synbiotic-treated patients. Metabolites pathway enrichment analysis showed that synbiotic significantly affected purine metabolism and aminoacyl-tRNA biosynthesis. And the purine metabolism and aminoacyl-tRNA biosynthesis were no longer significant differences in the Synbiotic group versus the healthy controls group. In conclusion, although littles influence on clinical parameters in the early intervention, the synbiotic showed a potential benefit to patients by ameliorating intestinal dysbiosis and metabolic defects; and the DI of intestinal microbiota is useful for the evaluation of the effect of clinical microbiota-targeting strategies on cirrhotic patients.Clinical Trial Registrationhttps://www.clinicaltrials.gov, identifiers NCT05687409.